Resposta :
Resposta:
Explicação passo a passo:
aₙ=a₁+(n-1)*r
19=-14+(n-1)*3
19+14=(n-1)*3
33=(n-1)*3
33/3=n-1
11=n-1
11+1=n
n=12 termos
Resposta:
[tex]\textsf{Segue a resposta abaixo}[/tex]
Explicação passo-a-passo:
[tex] \mathsf{ a_1=-14;~ a_n=19;~r=3;~ n=\,?}[/tex]
[tex] \mathsf{a_n=a_1+(n-1)\cdot r }[/tex]
[tex] \mathsf{ n=\dfrac{a_n-a_1}{r}+1}[/tex]
[tex] \mathsf{ n=\dfrac{19+14}{3}+1}[/tex]
[tex] \mathsf{n=\dfrac{33}{3}+1 }[/tex]
[tex] \mathsf{ n=11+1}[/tex]
[tex] \boxed{\boxed{\mathsf{ n=12}}}[/tex]